Historical. or Theoretical? The Separation and Unity of Powers in the Turkish Constitutions of 1921 and 1924 - (:unkn) unknown (AHMET YESEVI UNIV, 2011)
Although the beginning of modern constitutional movements in Turkey started in the same period with that of many European countries, the Turkish constitutional development bears its own peculiar historical and societal effects in many respects. Among others, one is the existence of the unity of powers in the constitutions of 1921 and 1924. A great number of commentators suggest that this was due to consequences of the conditions of that period. This paper argues that, unlike the common interpretation, the constitutional principle of the unity of powers in the 1921 and 1924 constitutions was defended on the basis of theoretical, philosophical and normative arguments, rather than on the necessity of such historical facts. The first part of the paper examines widely accepted comments with respect to the unity of powers in these constitutions; the second part discusses the historical development of the idea of the separation and unity of powers; the third part argues that the main reason behind the argument defended by Ataturk and his colleagues with respect to the unity of powers rested not on the conditions of war or concern for an effective government, but on a Rousseauian idea of sovereignty.
Keywords: Unity of Powers; Separation of Powers; The Constitutions of 1921 and 1924; Sovereignty; Ataturk